The teacher and the society of control. “what is hidden in what is seen” - Zambrano Leal, Armando (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In order to understand the uneasiness and the tensions faced in the teaching profession, it is important, required, and urgent to reflect on the transition occurred between the modern educational ideal and the contemporary one. The dissertation is focused on four aspects: the teacher’s trade, the teacher as a philosopher of the Republic, the teacher as a professional of the discipline, and the regime of proletarianization and control. These four aspects have as territory the structural isomorphism.